Avaliação de Programa de Gerenciamento de Casos Crônicos emplano de saúde do tipo autogestão em Minas Gerais - Paulo Magno do Bem Filho (2007)
The Health Care Systems of several countries are facing a crisis that results from a growing difficulty in financing the attendance to their citizens' health with consequent need of implementation of adjustments and reforms. The financial supporters of health care services are also questioning another aspect of the crisis in the present day model: the attendance from doctors and hospitals with an excessively technical approach and out of context of patients life history. These aspects have also been reinforcing the need of implementation of actions toward a more humanized medical practice. This study presents two articles. The first one discusses the insertion of home care on the management of patients with special needs due to specific chronic conditions (chronic cases). Home Care can be compatible and synergistic to the management of chronic diseases and cases. In this modality of health care, the multi professional work is centered in pro-active actions to attend needs perceived or not by patients or their families, and facilitates adherence to treatment protocols, reducing complications andpromoting a better quality of life. The second article presents the results of a case management program of a private health care plan in Minas Gerais, Brazil. From July 2002 to October 2005 83 patients were included in the program. Of these, 40 were male (48,2%) and 43 were female (51,8%). Age ranged from 42 to 98 years (77,3 +/- 3,9 years). There were 24 (28,9%) deaths, 24 patients (28,9%) were discharged and 35 (42,2%) stayed in the program at the end of this study. Multivariate analysis showed that a higher chance of deaths was significantly associated with severity of dependence of activities for daily life (ADL) at the admission in the program (p = 0,023), worsening of the degree of dependence of ADL while in the program (p = 0,024), dependence to get up (p = 0,008), need of caretaker (p = 0,003) and need of oxygen therapy (p = 0,003) while in the program. The higher chance of deaths associated with these variables reflects the inclusion of patients with conditions of higherseverity in the program as, for instance, patients with advanced cancer (10,8%) with terminal disease. Moreover, patients' inclusion in this health care plan program aimed to provide a more humanized attendance to the patients and did not have the reduction of costs as the only objective.